A supportive climate may protect employees’ well-being from negative humour events: A test of the affective events theory with humour events - Junça Silva, A.; Caetano, A.; Lopes, M. (European Journal of Humour Research, 2022)
This study investigated: (a) the mediating role of affect between humour events and well-being at work and (b) the moderating role of psychological work climate in the indirect relationship between humour events and well-being at work, via affect. The moderated mediation model was tested through a study with 93 full-time employees. We used regressions and bootstrapping analyses to test the moderated mediation model. The findings indicated a significant association between humour events and well-being at work with affect as a mediator. Moreover, psychological work climate was found to significantly moderate the indirect relationship between humour events and well-being at work via affect, such that it becomes stronger when individuals were in a positive psychological work climate. This paper adds considerable evidence of the relationship between humour-related events and their impact on individuals’ well-being. Psychological work climate strengthens the association between affect and well-being after humour events.